CD146 is a Novel ANGPTL2 Receptor that Promotes Obesity by Manipulating Lipid Metabolism and Energy Expenditure. Issue 6 (27th January 2021) - Wu, Zhenzhen; Liu, Jingyu; Chen, Gang; Du, Junfeng; Cai, Huiyun; Chen, Xuehui; Ye, Gaoqi; Luo, Yongting; Luo, Yiyi; Zhang, Liwen; Duan, Hongxia; Liu, Zheng; et al.
Abstract: Obesity and its related complications pose an increasing threat to human health; however, targetable obesity‐related membrane receptors are not yet elucidated. Here, the membrane receptor CD146 is demonstrated to play an essential role in obesity. In particular, CD146 acts as a new adipose receptor for angiopoietin‐like protein 2 (ANGPTL2), which is thought to act on endothelial cells to activate adipose inflammation. ANGPTL2 binds to CD146 to activate cAMP response element‐binding protein (CREB), which then upregulates CD146 during adipogenesis and adipose inflammation. CD146 is present in preadipocytes and mature adipocytes, where it is mediated by its ligands ANGPTL2 and galectin‐1. In preadipocytes, CD146 ablation suppresses adipogenesis, whereas the loss of CD146 in mature adipocytes suppresses lipid accumulation and enhances energy expenditure. Moreover, anti‐CD146 antibodies inhibit obesity by disrupting the interactions between CD146 and its ligands. Together, these findings demonstrate that ANGPTL2 directly affects adipocytes via CD146 to promote obesity, suggesting that CD146 can be a potential target for treating obesity. Abstract : The membrane receptor CD146 is a novel ANGPTL2 receptor that promotes obesity and insulin resistance. By interacting with ANGPTL2 and galectin‐1, CD146 enhances adipogenesis and lipogenesis while suppressing FAO and BAT thermogenesis. Furthermore, the disruption of the interaction between CD146 and its ligands by knocking out CD146 or using anti‐CD146 antibodies may prevent obesity and its related complications.